Study of herbivory on the radicalis palm (Chamaedorea radicalis) Mart., in the Sierra Madre Oriental of Tamaulipas, Mexico - Sánchez-Ramos, Gerardo; Reyes-Castillo, Pedro; Mora Olivo, Arturo; Martínez-Ávalos, José Guadalupe (Instituto de Ecología, A.C., 2010)
Rates of insect herbivory (% of leaf area eaten per day) were measured on the radicalis palm (Chamaedorea radicalis Mart.), during three seasons: early and late rainy season and the middle of the dry season at two different sites: temperate and tropical deciduous forest within the state of Tamaulipas, Mexico. In addition, some structural plant parameters (height, cover and diameter stem), physical plant parameters (foliar toughness and water content) and chemical plant parameters (nitrogen and phenols content) were measured, these parameters were correlated with timely (punctual) herbivory measurements. Results from this study show that the early wet season had the most feeding damage (0.17% per day); whereas, the dry season had the least damage (0.09% per day). The rate of herbivory per day during the middle of the wet season was 0.13%. These values are greater than those commonly reported from such habitats. The highest plants (1.1 times more), but with the least covers corresponded to the tropical deciduous forest. Within the tropical semideciduos forest this specie cover 2% of understory, whereas to the temperate forest cover 4%. In addition, nitrogen, phenol, and water content of leaves decreased as the season progressed; whereas, leaf toughness increased. We found leaf toughness during the late rainy season and the dry season to be the most effective repellent to herbivory